2008
DOI: 10.1128/aem.00486-08
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Imposed Salinity Gradients on Dissimilatory Arsenate Reduction, Sulfate Reduction, and Other Microbial Processes in Sediments from Two California Soda Lakes

Abstract: Volume 73, no. 16, p. 5130-5137, 2007. Page 5134: A miscalculation was made during the conversion of units for the measured N 2 O concentrations in sediment denitrification bioassays reported in Fig. 4B and the associated discussion in the text. The reported N 2 O production rates are too high by a factor of 1/0.028, or 36-fold, as they were not corrected for the headspace volume of the bioassay serum bottles (28 ml). The correct ranges of N 2 O production rates are 0.001 to 1.8 mol cm Ϫ3 day Ϫ1 for Mono Lake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 0 publications
2
39
0
Order By: Relevance
“…Mono Lake and Searles Lake, Kulp et al (2007) found different results. They observed a reduction of the SRR in Mono Lake with increasing salinity and no SRR at all was measured in Searles Lake, in which the sulfate reduction activity seemed to be inhibited by the high concentrations of borate.…”
Section: Microbial Diversity Along a Salinity Gradientmentioning
confidence: 89%
“…Mono Lake and Searles Lake, Kulp et al (2007) found different results. They observed a reduction of the SRR in Mono Lake with increasing salinity and no SRR at all was measured in Searles Lake, in which the sulfate reduction activity seemed to be inhibited by the high concentrations of borate.…”
Section: Microbial Diversity Along a Salinity Gradientmentioning
confidence: 89%
“…These results showed that bacterial release into the effluent sample may be due to substrate concentration limitation after biodegradation. The rate of biodegradation is highly variable and depends on many parameters including chemical structure and concentration of the organic substance in water samples, applied oxidant (ozone, chlorine) dose, temperature, salinity, pH, concentration of oxygen, and inorganic nutrients and concentration of active microorganisms (Becker et al, 2006;Brandt et al, 2003Brandt et al, , 2004Kulp et al, 2007;Sanchez et al, 2007;Spain et al, 1980;Spain and Veld, 1983;Steiner and Sauer, 2001;Swindoll et al, 1988). Some organic compounds, especially aromatic compounds are rather resistant to natural biodegradation and biodegradation of a compound of the mixture can be strongly influenced by the presence of other components in the mixture (Tsai and Juang, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used genetic markers to study As transformation mechanisms [9,12,[14][15][16][17][18][19]. In this study, we present a genetic mechanism for As resistance and As transformation in the bacterial isolates.…”
Section: Detection Of Arsenic Marker Genesmentioning
confidence: 99%
“…Several researchers have studied As transformation mechanisms using genetic markers such as arsB and arsC genes in the ars operon for arsenic resistance [12,14], the arrA gene for dissimilatory As(V) respiration (DAsR) [15][16][17], and the aoxB gene for As(III) oxidation [18][19]. Moreover, some studies detected that in spite of clear evidence of the As-transforming activity by microorganisms, no amplicon for arsenite oxidase (aoxB) or As(V) respiratory reductase (arrA) was attained using the reported polymerase chain reaction (PCR) primers and protocols [17,[20][21].…”
Section: Introductionmentioning
confidence: 99%